2012
DOI: 10.1016/j.ajpath.2011.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Nuclear Receptor Coactivator AIB1/SRC-3 in Angiogenesis and Wound Healing

Abstract: The nuclear receptor coactivator amplified in breast cancer 1 (AIB1/SRC-3) has a well-defined role in steroid and growth factor signaling in cancer and normal epithelial cells. Less is known about its function in stromal cells, although AIB1/SRC-3 is up-regulated in tumor stroma and may, thus, contribute to tumor angiogenesis. Herein, we show that AIB1/SRC-3 depletion from cultured endothelial cells reduces their proliferation and motility in response to growth factors and prevents the formation of intact mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…NCOA3 is a p160SRC family homolog that functions as a nuclear receptor co-activator by interacting with steroid receptors and possesses an intrinsic histone acetyltransferase activity. 16, 17 Studies have demonstrated several roles for NCOA3, it is involved in the maintenance of pluripotency, 30 angiogenesis, wound healing, 31 metabolic defects 32 and immunomodulation. 33 NCOA3 locus is amplified in breast (9.5%) 34 and colorectal cancers (27.5% gain in copy number), 35 that highlights its oncogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…NCOA3 is a p160SRC family homolog that functions as a nuclear receptor co-activator by interacting with steroid receptors and possesses an intrinsic histone acetyltransferase activity. 16, 17 Studies have demonstrated several roles for NCOA3, it is involved in the maintenance of pluripotency, 30 angiogenesis, wound healing, 31 metabolic defects 32 and immunomodulation. 33 NCOA3 locus is amplified in breast (9.5%) 34 and colorectal cancers (27.5% gain in copy number), 35 that highlights its oncogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…However, less is known about the SRC-3 function in stroma. A recent study elucidates the role of SRC-3 in angiogenesis and wound healing 58 . SRC-3 was shown to promote proliferation and motility of endothelial cells, such that neoangiogenesis was dependent on the presence of SRC-3 58 .…”
Section: Src-3 Impacts Multiple Axes In Cancermentioning
confidence: 99%
“…A recent study elucidates the role of SRC-3 in angiogenesis and wound healing 58 . SRC-3 was shown to promote proliferation and motility of endothelial cells, such that neoangiogenesis was dependent on the presence of SRC-3 58 . The study also demonstrated that both alleles of SRC-3 were required for proper wound healing in vivo and that SRC-3 may cross-talk with FGF (fibroblast growth factor) signaling to regulate wound healing process 58 .…”
Section: Src-3 Impacts Multiple Axes In Cancermentioning
confidence: 99%
“…SRC‐3 integrates multiple signaling pathways to regulate cell proliferation, migration and invasion (Zhou et al, ; Long et al, ), and has been characterized as a bona fide oncogene with amplification and/or overexpression in multiple human cancers (Anzick et al, ; Torres‐Arzayus et al, ; Tien and Xu, ). In addition to its functions in epithelial cells, SRC‐3 was also shown to be important for the functions of endothelial cells including in vivo angiogenesis (Fereshteh et al, ; Ying et al, ; Al‐Otaiby et al, ). The molecular mechanisms underlying SRC‐3's function in endothelial cells, however, are largely unknown.…”
mentioning
confidence: 99%
“…The role of ERK3 signaling in angiogenesis, however, remains to be explored. Importantly, both of the two known EKR3 substrates, SRC‐3 and MK5, are known to positively regulate angiogenesis (Al‐Otaiby et al, ; Yoshizuka et al, ), suggesting that ERK3 may play a similar role in this process. The functional activity of a protein kinase is regulated by both its gene expression level and its protein enzymatic activation.…”
mentioning
confidence: 99%